A clinico-epidemiological study of the first outbreak of Nipah virus in India – report from ground zero - Saha, Rama; Mitra, Sudipan; Halder, Swapan; Deb, Jaydip; Patra, Anupam; narayan Sarkar, Gautam (International Journal of Medical Research and Review, 2020)
Introduction: The first Nipah Virus (NiV) outbreak occurred in India in the year 2001 at Siliguri. The second outbreak happened at Nadia in 2007. Nipah Virus exhibits neurological and pneumonic tropism with the predominant clinical presentation being encephalitis in humans. Material and Methods: The present study was a record based prospective study on 67 cases admitted with pyrexia of unknown origin in North Bengal Medical College during the period from 18.02.2001 to 30.02.2001 and a parallel study on epidemiological record carried out by PSM department also taken into account. All necessary investigations including autopsy examination, pathological, and microbiological study were done. Results: There was a clustering of cases around Bhaktinagar. There was a strong H/O Medinova Nursing Home Contact among the patients. 18 out of 20 cases were staff of that Nursing Home. Serum samples tested show NiV specific IgM and IgG in 9 out of 17 samples with one sample which was positive for IgG only suggesting past infection. The cases were admitted with predominant neurological symptoms (53.73% cases) but about 80% recovered with no residual neuro deficit. The natural reservoir of NiV is present in Bangladesh and in Northern India. Conclusion: When NiV infection is suspected, infection control practices must be strengthened to avoid an outbreak in a hospital setting. Here the present study is presenting the experience in the first outbreak of the Nipah virus in India at Siliguri for awareness of clinical personnel to control further outbreak at the very beginning.